1997
DOI: 10.1128/mcb.17.12.6773
|View full text |Cite
|
Sign up to set email alerts
|

The Polycomb Group Protein Complex of Drosophila melanogaster Has Different Compositions at Different Target Genes

Abstract: In Drosophila the Polycomb group genes are required for the long-term maintenance of the repressed state of many developmental regulatory genes. Their gene products are thought to function in a common multimeric complex that associates with Polycomb group response elements (PREs) in target genes and regulates higherorder chromatin structure. We show that the chromodomain of Polycomb is necessary for protein-protein interactions within a Polycomb-Polyhomeotic complex. In addition, Posterior Sex Combs protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
90
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 62 publications
8
90
1
Order By: Relevance
“…(5,37). Consistent with this possible mechanism, SUV39H1 associates with M31 (HP1␤), the only other characterized mammalian su(var) homolog (1), and their cosedimentation supports participation in a su(var) complex distinct from two previously described mammalian PcG complexes (45,46). When SUV39H1 is forcibly expressed under our experimental conditions, it accumulates in distinct nuclear bodies that are large and electron dense, with ultrastructural features suggestive of heterochromatin.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…(5,37). Consistent with this possible mechanism, SUV39H1 associates with M31 (HP1␤), the only other characterized mammalian su(var) homolog (1), and their cosedimentation supports participation in a su(var) complex distinct from two previously described mammalian PcG complexes (45,46). When SUV39H1 is forcibly expressed under our experimental conditions, it accumulates in distinct nuclear bodies that are large and electron dense, with ultrastructural features suggestive of heterochromatin.…”
Section: Discussionsupporting
confidence: 52%
“…The repressor property of SUV39H1 localized to its amino-terminal half which also contains a chromo domain, a modular motif that self-associates and assembles into multimeric complexes on chromatin (31,39,46). Notably, transcriptional repression by SUV39H1 did not require its SET domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Context Mirror predicts the PHO/SFMBT interaction (Alfieri et al, 2013) and the well-characterized interactions between these two subunits of the PhoRC complex and those of PRC1: PHO/PC (Mohd-Sarip et al, 2002), PHO/PH-P (Mohd- Sarip et al, 2002) and SFMBT/SCM (Grimm et al, 2009). The bioinformatic method also predicts the well-established interactions between subunits of the PRC1 complex, that is, PH-P/PC (Strutt and Paro, 1997), PH-P/PSC (Kyba and Brock, 1998), PH-P/SCM (Peterson et al, 1997), PC/PSC (Kyba and Brock, 1998), PC/SCE and PSC/SCE (Gorfinkel et al, 2004). In contrast, no interaction is predicted between the two subunits of the PR-DUB complex, although the N-terminal region of ASX is directly involved in its interaction with CALYPSO (Scheuermann et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The advent of ChIP maps demonstrated an accumulation of PcG/TrxG proteins at PREs and some of the associated promoters (18,19). Interestingly, PcG proteins were found to be bound at PREs, even if the associated gene was active (20,21). In addition, a recent study that concentrated on the HOX gene Ultrabithorax (Ubx) in Drosophila imaginal discs showed that members of the PRC1/2 complexes and Trx are constitutively bound at the regulatory sites of Ubx regardless of its activity state (16).…”
mentioning
confidence: 99%